2009
DOI: 10.1002/ccd.21898
|View full text |Cite
|
Sign up to set email alerts
|

Orbital atherectomy for infrapopliteal disease: Device concept and outcome data for the OASIS trial

Abstract: Objective: The purpose of this study was to assess the safety and short-term efficacy of orbital atherectomy for chronic infrapopliteal arterial occlusive disease. Background: Infrapopliteal occlusive disease is a common cause of critical limb ischemia and claudication. There are no American College of Cardiology/American Heart Association guidelines for infrapopliteal revascularization for chronic limb ischemia. Methods: One hundred twenty four patients (201 stenoses) were enrolled in a prospective non-random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 23 publications
1
66
1
1
Order By: Relevance
“…17 In the OASIS trial orbital AT had satisfactory results in infrapopliteal lesions, nevertheless adjunctive balloon angioplasty was performed after plaque modification only in 42.6%. 18 In the CALCIUM 360 trial, the infra-popliteal arteries in 50 patients with CLI were qualified to plaque modification with subsequent balloon angioplasty vs. balloon angioplasty alone. 19 In that study the AT group had a lower rate of target vessel revascularization and all-cause mortality in comparison with balloon angioplasty alone.…”
Section: Resultsmentioning
confidence: 99%
“…17 In the OASIS trial orbital AT had satisfactory results in infrapopliteal lesions, nevertheless adjunctive balloon angioplasty was performed after plaque modification only in 42.6%. 18 In the CALCIUM 360 trial, the infra-popliteal arteries in 50 patients with CLI were qualified to plaque modification with subsequent balloon angioplasty vs. balloon angioplasty alone. 19 In that study the AT group had a lower rate of target vessel revascularization and all-cause mortality in comparison with balloon angioplasty alone.…”
Section: Resultsmentioning
confidence: 99%
“…This percutaneous, minimally invasive endovascular device system is composed of a single-use, low-profile catheter with a diamond-coated crown that orbits at high speeds while removing a thin layer of calcific plaque with each pass of the crown [8]. Randomized clinical trial (RCT) evidence indicated that CLI patients receiving BA plus atherectomy involving OAS had a lower rate of complications [9][10][11][12], and medial damage [8], and reduced need for bailout stenting [12], thus preserving future treatment options.…”
Section: Figure 1 Economic Model Scaffoldmentioning
confidence: 99%
“…It is a grinding-type device with rotational speed in the range 80,000-200,000 rpm that is controlled by a pressure valve. An eccentric diamondcoated crown is responsible for grinding: by increasing the rotational speed, lumen diameter can be increased by 1.75 times the device diameter (Safian et al 2009). Tool diameter ranges from 1.25 to 2.5 mm and the unprotected shaft portion, driven by a compressed gas turbine, is limited to 6 cm.…”
Section: Orbital Atherectomymentioning
confidence: 99%